Bir yarı açık oyuk içindeki ayrık ısıtıcıdan taşınımla ısı geçişi - Gül, Samet (Fen Bilimleri Enstitüsü, 2001)
An understanding of natural convective heat transfer is essential for the proper design of passive heating and cooling applications in energy systems. Natural convection caused by external heating and/or internal heat sources in a closed or open cavity, is of practical importance in fire safety, building energy systems, cooling of electronic equipment, environmental engineering, nuclear engineering and other applications. In this study, a square box with one of its side walls opened at the upper and lower 1/4 portions has been considered as the open cavity, and a discrete horizontal heating bar with square cross-section as the internal heat source. All the walls of the cavity are assumed adiabatic. In the numerical analysis, where the CFD package FLUENT 4.5 was used, the location of the square source was altered. Numerical flow and temperature field visualization samples are presented in section four respectively each for a different heat source location. For each location of the heat source, it is observed that the fluid flow entering the cavity is induced towards the heat source. When the heat source is at location 1, this effect causes the bottom floor of the cavity to be swept thoroughly by the fresh fluid and a displacement flow is established through the cavity. For location 2, however, this effect causes a dead space to be left at the lower left corner of the cavity. The Nu numbers for the case in which the heat source is at location 1 are the smallest. Streamlines at location 1 show that the bottom and left surfaces of the heat source are subject to weak flows due to the hydrodynamic resistance of the narrow gap between the heater surface and cavity walls.

Bilindiği üzere doğal taşımınla ısı geçişi, enerji sistemlerindeki pasif ısıtma ve soğutma uygulamaların kusursuz tasarımı için esas teşkil eder. Açık veya kapalı oyuk içindeki ısıtıcıyla ya da dışardan ısıtmayla oluşan doğal taşınım; yangın güvenliğinde,bina enerji sistemlerinde elektronik devrelerin soğutulmasında,nükleer ve çevre mühendisliklerinde ve diğer uygulamalarda öneme haizdir. Bu çalışmada, bir kenarı altından ve üstünden 1/4 oranında açık olan kare şeklindeki kutu içine bir ayrık bir ısıtıcı yerleştirilmiştir. Bütün oyuk duvarları adyabatik kabul edilmiştir. Sayısal çözümler için, ısıtıcının konumu değiştirilerek FLUENT 4.5 paket programı kullanılmıştır. Isıtıcı kaynağın farklı konumlardaki akış ve sıcaklık alanlarının sayısal örnekleri bölüm 4'te gösterilmiştir. Her konum için oyuğa giren akışkanın ısıtıcıya doğru yöneldiği gözlenmiştir. Bu etkiden dolayı Konum Ficin yapılan çözümlerde oyuğun tabanındaki akışkanın taze akışkanla süpürülerek oyuk boyunca bir yer değiştirmeli akış gerçekleştiği görülmüştür. Bu etki Konum 2'de köşelerde ölü bölgeler oluşmasına neden olmaktadır. En düşük Nusselt sayılan konum l'dedir. Konum l'de ısıtıcı ve oyuk duvarları arasındaki boşluktan kaynaklanan hidrodinamik direnç ısı taşınımını zayıflatmaktadır.
Convective heat transfer in a partially open cavity
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2001
Keywords: Doğal taşınım; Enerji sistemleri; Isı geçişi; Isıtıcılar; Natural convection; Energy systems; Heat transfer; Calorifics